Ramsay Hunt Syndrome: A Rare Case of Otalgia - Duarte, Leonor Luz; Rebelo, Catarina Calheno; Ferreira, Maria Inês; Oliveira, Nuno (Gazeta Médica, 2020)
Ramsay Hunt syndrome is an uncommon cause of otalgia and is described as a triad of otalgia, ipsilateral peripheral facial paralysis and vesicular rash in the external ear or oropharynx, caused by the reactivation of the Varicella-Zoster Virus. We report the case of a 21-year-old man who attended a consultation with his family doctor with a one-week history of right sided otalgia, being diagnosed with otitis externa and treated with topical antibiotics. Two days later, he developed right peripheral facial paralysis, and was diagnosed with Ramsay Hunt Syndrome. This syndrome is an emerging and potentially serious medical condition that requires an early approach and treatment. Its diagnosis is clinical and its treatment includes antiviral drugs and corticosteroids. The treatment is often postponed, associated with a worse prognosis and possible complications, such as post-herpetic neuralgia, corneal exposure ulcers and neurological sequelae.